Front Cover: Dielectrophoretic characterization and isolation of jellyfish stinging capsules. Issue 16 (21st August 2017) - Park, Sinwook; Capelin, Daniel; Piriatinskiy, Gadi; Lotan, Tamar; Yossifon, Gilad
Abstract : Electrophoresis 2017, 38, 1996–2003. DOI:10.1002/elps.201700072 The front cover picture shows the dielectric characterization of jellyfish stinging capsules using a quadrupole microelectrode array in terms of dielectrophoretic (DEP) and electrorotational (ROT) spectra with best fits derived from theoretical models. The difference in the DEP response of different capsule sizes can then be used as an efficient tool for separation of a specific capsule type from a heterogeneous population using a microfluidic platform. Such purification and collection of nematocyst sub‐populations is essential for further biochemical analysis.